2022
DOI: 10.1002/adma.202108586
|View full text |Cite
|
Sign up to set email alerts
|

Triboresistive Touch Sensing: Grid‐Free Touch‐Point Recognition Based on Monolayered Ionic Power Generators

Abstract: been applied more closely to the human body. Owing to the soft and curved nature of human skin, the systems need to be flexible, robust, and transparent to ensure operational reliabilities and to provide comforts. [3,4] However, it has been challenging to ensure these desirable properties due to the complicated structures of conventional touch-sensing systems, which contain a network of individual electrodes and stacked multilayers. [4,5,8,10,12] More importantly, sensing systems inevitably rely on external po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…First, we found a distance-sensitive output voltage of the S-TENG because the electric displacement field depends on the contact position's distance and the relatively high electric resistance of the PVC-gel. [45] As shown in Figure 5d, the output voltage, as a function of the distance between the touch point and electrode, is inversely proportional to the distance. The open-circuit voltage based on the distances of the S-TENG can be expressed as…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…First, we found a distance-sensitive output voltage of the S-TENG because the electric displacement field depends on the contact position's distance and the relatively high electric resistance of the PVC-gel. [45] As shown in Figure 5d, the output voltage, as a function of the distance between the touch point and electrode, is inversely proportional to the distance. The open-circuit voltage based on the distances of the S-TENG can be expressed as…”
Section: Resultsmentioning
confidence: 92%
“…First, we found a distance‐sensitive output voltage of the S‐TENG because the electric displacement field depends on the contact position's distance and the relatively high electric resistance of the PVC‐gel. [ 45 ] As shown in Figure 5d , the output voltage, as a function of the distance between the touch point and electrode, is inversely proportional to the distance. The open‐circuit voltage based on the distances of the S‐TENG can be expressed as where h is the gap distance, a n is the distance of the contact point on the PVC‐gel to the electrode “ n ”, S is the active area, and k is the Coulomb force constant, which are expressed in detail in Figure S17 and Note S6 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Sun et al reported a triboresistive touch sensor based on the ionic PDMS. 91 The ionic PDMS in that study was composed of hydrophilic PDMS and hydrophobic IL through H-bonding and van der Waals interactions (Fig. 9e).…”
Section: Stretchable Ionic Conductors (Sics)mentioning
confidence: 89%
“…To combine polymers with ILs, it is important to find appropriate interactions between the functional groups of polymers and ILs, as these interactions determine their compatibility. The polymers can be roughly classified as polymer-based type 52,74–88 and monomer-based type, 89–109 and the ILs are composed of diverse pairs of the cationic and the anionic units (Fig. 7a and b).…”
Section: Stretchable Ionic Conductors (Sics)mentioning
confidence: 99%
“…It is used in biomedicine [ 3 , 4 ], microfluidics [ 5 , 6 , 7 ], MEMS [ 8 ], triboelectricity [ 9 ] and piezoelectrics [ 10 ]. Motivation to explore the structure and dynamics of ionic PDMS [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] or other melts [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], is very high since ionic interactions inherit polymers with a functionality that leads to a high performance and applications as gas-separating membranes [ 15 ], water purification membranes [ 13 , 14 , 16 ], energy storage devices [ 39 , 40 ] as well as in sensing [ 22 , 23 ], actuation [ 21 ], fuel cells [ 41 ], and others [ 18 , 19 , 24 , 42 ].…”
Section: Introductionmentioning
confidence: 99%